The emergence and spread of blaNDM-1, blaKPC-2, mcr-10 genes, and the tmexCD2-toprJ2 gene cluster in extensively drug-resistant clinical Raoultella ornithinolytica - Ye, Yafei; Rao, Yuting; Fang, Lei; Ye, Haowei; Chen, Ruyan; Li, Chenyu; Shen, Yanhao; Jia, Yuanyuan; Guo, Xiaobing (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundRaoultella ornithinolytica is an infrequent opportunistic pathogen capable of causing multi-site infections and frequently harboring a broad array of resistance determinants, thereby complicating antimicrobial therapy. Here we report the genomic characterization of the extensively drug-resistant strain FAHZZU6693, which concurrently harbors blaNDM-1, blaKPC-2, mcr-10 genes and tmexCD2-toprJ2 resistance cluster.MethodsMatrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) and average nucleotide identity (ANI) were employed to confirm the species identity as R. ornithinolytica. Antimicrobial susceptibility testing (AST) delineated the corresponding antimicrobial phenotypes. S1 nuclease pulsed-field gel electrophoresis (S1-PFGE), Southern blotting and whole-genome sequencing (WGS) elucidated the isolate’s complete molecular architecture.ResultsGlobally, R. ornithinolytica strains harboring related resistance genes exhibit diverse geographical distribution. Strain FAHZZU6693 is resistant to most antibiotics, except amikacin and chloramphenicol. The blaNDM-1, blaKPC-2, mcr-10 genes and the tmexCD2-toprJ2 cluster in this strain are plasmid-borne. These occur in conserved genetic contexts: xerC-mcr-10-ISEc36-ISEc27-ISEcl1 and umuC-IS881-tmexC2-tmexD2-toprJ2-umuC. Further analysis indicates that the insertion sequence ISEc27 and the gene element umuC play a crucial role in the dissemination of the mcr-10 gene and the tmexCD2-toprJ2 gene cluster.ConclusionsThis study combines database analysis to comprehensively describe the distribution of R. ornithinolytica strains carrying the target genes and characterizes the genomic features of a clinically Multi-drug resistant strain, providing a theoretical foundation for preventing the spread of such bacteria.